New Analytical Methods for the Surface/ Interface and the Micro-Structures in Advanced Nanocomposite Materials by Synchrotron Radiation - K. Nakamae; J. Matsui; K. Yokoyama; Y. Urushihara; S. Kuwamoto; L. Li; S. Takeda (PPIKSN-BATAN, 2010)
Analytical methods of surface/interface structure and micro-structure in advanced nanocomposite materials by using the synchrotron radiation are introduced. Recent results obtained by the energy-tunable and highly collimated brilliant X-rays, in-situ wide angle/small angle X-ray diffraction with high accuracy are reviewed. It is shown that small angle X-ray scattering is one of the best methods to characterize nanoparticle dispersibility, filler aggregate/agglomerate structures and in-situ observation of hierarchical structure deformation in filled rubber under cyclic stretch. Grazing Incidence(small and wide angle) X-ray Scattering are powerful to analyze the sintering process of metal nanoparticle by in-situ observation as well as the orientation of polymer molecules and crystalline orientation at very thin surface layer (ca 7nm) of polymer film. While the interaction and conformation of adsorbed molecule at interface can be investigated by using high energy X-ray XPS with Enough deep position (ca 9 micron m).Received: 11 October 2010; Revised: 13 December 2010; Accepted: 23 December 2010